Finanças públicas : estudo da política fiscal no Espírito Santo nas décadas de 2000 e 2010 - Rasseli, Adriano Frossard (2017)
What factors and fiscal policy practices most contribute to the balance of public finances? This study aims to understand factors and fiscal policy practices in the last sixteen years that contributed to the fiscal balance situation in the State of Espírito Santo in the opinion of politicians and public managers in government during that period. The applied time cut is justified by the introduction in Brazilian fiscal federalism of Complementary Law No. 101 on May 4, 2000 (Fiscal Responsibility Law - LRF). The theoretical framework that bases this research is the macroeconomic literature dealing with fiscal policy, the discussion of its role in the conduct of economic policy in light of the main economic theories and the contextualization of the implementation of the LRF in Brazil. In order to achieve the research objective, the methodological approach used was qualitative, through interviews with people with knowledge and performance in the area of state public finances that had a leading role with technical and / or political participation in the conduct of Espírito Santo fiscal policy in the period researched. Through the transcription of the content of these interviews and the use of content analysis as a research technique, the technical product generated was the identification of the factors and fiscal policy practices in the last sixteen years that contributed to the current fiscal balance situation in Espírito Santo in the opinion of the research participants. The main factors identified were: the existence of a political influence predominantly favorable to fiscal balance; the institution of a fiscal responsibility culture; and the constitution of a technical team with qualified human resources to manage public finances and conduct the fiscal policy of Espírito Santo. Regarding fiscal policy practices specifically, those identified were: compliance with fiscal rules; adoption of a realistic and balanced budget; implementation of measures to control and reduce public spending; and efforts to increase revenue collection. The work also brings as relevant contributions reflections on: the political and the fiscal rules influence in the management of the public finances; the factors and fiscal policy practices that did not work or that contributed least to the situation of fiscal balance in Espírito Santo in that period; the future of Espírito Santo fiscal policy, and the role of the state in fiscal policy and in the economy